Dampak Intervensi Complementary Food pada Anak dalam Pencegahan Stunting - Grathima, Eishca Fanani; Yunitasari, Esti; Indarwati, Retno (Journal of Telenursing (JOTING), 2024)
This study explores the importance of providing appropriate complementary foods in preventing stunting during the transition period from exclusive breastfeeding to complementary foods. This research uses a literature review method with electronic databases and websites, namely Ebsco, Scopus, Proquest, and PubMed. The study's results showed that intensive complementary feeding during the first 1000 days of life effectively prevented stunting. This research highlights the combination of Behavior Change Communication (BCC) interventions and education for mothers and families as critical factors for success in preventing stunting. This research recommends the importance of varying complementary food choices adapted to the living environment's characteristics during the first 1000 days of life, as well as the role of health workers in providing BCC in the community. The conclusion is that intensive complementary feeding during the first 1000 days of life, supported by BCC and education interventions, as well as a variety of food choices that are appropriate to the environment, is effective in preventing stunting. Keywords: Stunting, MPASI, Intervention